Trait Acclimation Mitigates Mortality Risks of Tropical Canopy Trees under Global Warming - Sterck, Frank; Anten, Niels P. R.; Schieving, Feike; Zuidema, Pieter A. (Frontiers in Plant Science, 2016)
There is a heated debate about the effect of global change on tropical forests. Many scientists predict large-scale tree mortality while others point to mitigating roles of CO2 fertilization and – the notoriously unknown – physiological trait acclimation of trees. In this opinion article we provided a first quantification of the potential of trait acclimation to mitigate the negative effects of warming on tropical canopy tree growth and survival. We applied a physiological tree growth model that incorporates trait acclimation through an optimization approach. Our model estimated the maximum effect of acclimation when trees optimize traits that are strongly plastic on a week to annual time scale (leaf photosynthetic capacity, total leaf area, stem sapwood area) to maximize carbon gain. We simulated tree carbon gain for temperatures (25-35ºC) and ambient CO2 concentrations (390-800 ppm) predicted for the 21st century. Full trait acclimation increased simulated carbon gain by up to 10-20% and the maximum tolerated temperature by up to 2ºC, thus reducing risks of tree death under predicted warming. Functional trait acclimation may thus increase the resilience of tropical trees to warming, but cannot prevent tree death during extremely hot and dry years at current CO2 levels. We call for incorporating trait acclimation in field and experimental studies of plant functional traits, and in models that predict responses of tropical forests to climate change.